2020
DOI: 10.1021/acsami.0c04796
|View full text |Cite
|
Sign up to set email alerts
|

Antibuoyancy and Unidirectional Gas Evolution by Janus Electrodes with Asymmetric Wettability

Abstract: The bubbles electrochemically generated by gas evolution reactions are commonly driven off the electrode by buoyancy, a weak force used to overcome bubble adhesion barriers, leading to low gas transporting efficiency. Herein, a Janus electrode with asymmetric wettability has been prepared by modifying two sides of a porous stainless-steel mesh electrode, with superhydrophobic polytetrafluoroethylene (PTFE) and Pt/C (or Ir/C) catalyst with well-balanced hydrophobicity, respectively; affording unidirectional tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…The catalyst was loaded with 2 mg cm -2 , a layer of polytetrafluoroethylene (PTFE) solution was deposited on the same side (Figures S36 and S37, Supporting Information) to make the catalyst side hydrophobic to construct Janus electrode which can work both as a gas diffusion electrode (GDE) and the working electrode. [29] It was found that the droplet contact angle increased from 88.6°to 137°after PTFE modifi-cation (Figure 5b, illustration). Then, the Janus electrode with asymmetric wettability was used to conduct electrolysis in H-cell.…”
Section: The Orr Performance Evaluated In H-cellmentioning
confidence: 95%
“…The catalyst was loaded with 2 mg cm -2 , a layer of polytetrafluoroethylene (PTFE) solution was deposited on the same side (Figures S36 and S37, Supporting Information) to make the catalyst side hydrophobic to construct Janus electrode which can work both as a gas diffusion electrode (GDE) and the working electrode. [29] It was found that the droplet contact angle increased from 88.6°to 137°after PTFE modifi-cation (Figure 5b, illustration). Then, the Janus electrode with asymmetric wettability was used to conduct electrolysis in H-cell.…”
Section: The Orr Performance Evaluated In H-cellmentioning
confidence: 95%
“…[1] Achieving state-of-the-art catalytic performance requires high intrinsic activity and fast mass transport at low and large current densities [2] with key contributing factors including inherent electronic structure, [3] intermetallic synergy, [4] active site-intermediate interaction, [5,6] electrolyte-catalyst interfacial charge transfer, [7,8] in situ phase transformation and surface reconstruction, [9,10] as well as surface gas bubble behavior. [11] structural evolution to the more active β -NiOOH and γ -FeOOH phases, and the iv) provision of a superhydrophilic surface for ultrafast gas bubble growth and release during OER.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32] A gas-repelling catalyst can reduce the surface tension and proportionally the adhesion force toward gas bubbles, significantly altering the underwater gas bubble dynamics (smaller bubbles) and their detachment rate (bursting state). [33][34][35] Despite the paramount influence of gas bubble effect, the behavior of gas bubbles on electrode surfaces has not been well-understood, partly due to the lack of in situ characterization techniques. While external optical imaging provides some valuable information on the late-state gas bubble behavior, the early stage of gas bubble evolution on catalyst surfaces and how it affects the electrocatalysis, are yet to understand.…”
Section: Introductionmentioning
confidence: 99%